Determination of the Quality of Cooking Oil in View from the Bias Index Parameters - Husna, Salsabila; Muhammad Iqbal Fauzi; Bayu Setiaji (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to test the quality of cooking oil using the parameter of refractive index by utilizing a simple refractometer constructed from mica plastic sheets. The principle of testing cooking oil is based on Snell's law. The cooking oil samples used were four brands of cooking oil with new conditions which were labeled A, B, C, and D. of poor quality, cooking oil B with a refractive index of 1.547 refers to source 1 having good quality and when referring to source 2 it has poor quality, and cooking oil C with a refractive index of 1.494 refers to both sources having good quality. Therefore, it can be concluded that cooking oil C has the best quality than the other three cooking oil samples.